2017
DOI: 10.3389/fpls.2017.01768
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Rhizobacteria in Amelioration of Salinity Stress: A Systems Biology Perspective

Abstract: Salinity affects plant growth and is a major abiotic stress that limits crop productivity. It is well-understood that environmental adaptations and genetic traits regulate salinity tolerance in plants, but imparting the knowledge gained towards crop improvement remain arduous. Harnessing the potential of beneficial microorganisms present in the rhizosphere is an alternative strategy for improving plant stress tolerance. This review intends to elucidate the understanding of salinity tolerance mechanisms attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
319
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 459 publications
(332 citation statements)
references
References 124 publications
(140 reference statements)
9
319
0
4
Order By: Relevance
“…). Our results confirmed that PGPR can minimize the negative effects of abiotic stresses, as previously indicated ( Qin et al, ; Ilangumaran and Smith , ). The rhizobacteria used in this study were resistant to salt stress (Tab.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…). Our results confirmed that PGPR can minimize the negative effects of abiotic stresses, as previously indicated ( Qin et al, ; Ilangumaran and Smith , ). The rhizobacteria used in this study were resistant to salt stress (Tab.…”
Section: Discussionsupporting
confidence: 92%
“…Salt stress induces the accumulation of Na + ions and nutritional imbalance in plant tissues, water content loss, and finally growth suppression and yield reduction ( Cuartero and Fernández‐Muñoz , ). Multiple studies have reported that the use of selected PGPR strains may alleviate salt stress in crops ( Qin et al, ; Ilangumaran and Smith , ).…”
Section: Introductionmentioning
confidence: 99%
“…). PGPR can induce salinity stress tolerance through the modulation of physiological and biochemical process (Ilangumaran and Smith ). They can also induce systemic resistance (Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…auxin, cytokinin, ethylene and gibberellins), nitrogen fixation, nutrient mobilization and siderophore production (Hayat et al 2010). PGPR can induce salinity stress tolerance through the modulation of physiological and biochemical process (Ilangumaran and Smith 2017). They can also induce systemic resistance (Yang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Plants in their natural environment are colonized by a wide array of microbes, including nitrogen-fixing bacteria, endophytes (Ilangumaran & Smith, 2017). Arbuscular mycorrhizal fungi are ubiquitous among the vast array of microbes inhabiting the rhizosphere of the plants (Egamberdieva, Wirth, Li, Abd-Allah, & Lindström, 2017).…”
Section: Introductionmentioning
confidence: 99%